Exposure of Physicians to Workplace Violence - Marta Milošević; Anamarija Petek Erić (Southeastern European Medical Journal)
Introduction: The main goal of the research was to determine whether the doctors who work at the Clinical Medical Center Osijek are exposed to violence in the workplace, in what form of violence, whether there are differences in exposure between doctors according to age, gender and depending on whether they are specialists or residents.